2015
DOI: 10.1016/j.bbadis.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Heart mitochondria and calpain 1: Location, function, and targets

Abstract: Calpain 1 is an ubiquitous Ca(2+)-dependent cysteine protease. Although calpain 1 has been found in cardiac mitochondria, the exact location within mitochondrial compartments and its function remain unclear. The aim of the current review is to discuss the localization of calpain 1 in different mitochondrial compartments in relationship to its function, especially in pathophysiological conditions. Briefly, mitochondrial calpain 1 (mit-CPN1) is located within the intermembrane space and mitochondrial matrix. Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 95 publications
4
39
0
Order By: Relevance
“…201, 205, 206 An increase of Omi/HtrA2 (an intermembrane space protease) content enhances cardiac injury in aged hearts compared to adult hearts. 207 In contrast, loss of HtrA2/Omi causes premature aging.…”
Section: Mitochondrial Biogenesis Dynamics and Removalmentioning
confidence: 99%
“…201, 205, 206 An increase of Omi/HtrA2 (an intermembrane space protease) content enhances cardiac injury in aged hearts compared to adult hearts. 207 In contrast, loss of HtrA2/Omi causes premature aging.…”
Section: Mitochondrial Biogenesis Dynamics and Removalmentioning
confidence: 99%
“…Calpain I has been identified in the IMS where it will cleave AIF and NCLX, thereby increasing apoptosis and matrix Ca 2+ levels (Kar et al 2010). More recently, Chen et al separated mitochondrial compartments using digitonin, combined with ultra-centrifugation identified calpain I to be in the matrix along with the small subunit calpain IV, and the endogenous calpain inhibitor calpastatin (Chen and Lesnefsky 2015). It was also identified that upon reperfusion the mitochondrial ND6 subunit of complex I is digested in a calpain-dependent manner (Arrington et al 2006; Chen and Lesnefsky 2015; Shintani-Ishida and Yoshida 2015).…”
Section: Ca2+ As Key To Regulation Of the Mptpmentioning
confidence: 99%
“…More recently, Chen et al separated mitochondrial compartments using digitonin, combined with ultra-centrifugation identified calpain I to be in the matrix along with the small subunit calpain IV, and the endogenous calpain inhibitor calpastatin (Chen and Lesnefsky 2015). It was also identified that upon reperfusion the mitochondrial ND6 subunit of complex I is digested in a calpain-dependent manner (Arrington et al 2006; Chen and Lesnefsky 2015; Shintani-Ishida and Yoshida 2015). However, the specific residues, and site of action of calpain-mediated cleavage is yet to be identified leaving the possibility of an IMS site of action.…”
Section: Ca2+ As Key To Regulation Of the Mptpmentioning
confidence: 99%
“…Desmin as other cytoskeletal proteins has been hypothesized to reproducibly degenerate into the same degradation products, upon the activity of the Ca 2+ dependent calpains [10] that have been localized in heart mitochondria [11] . These recent data suggest that calpains in the heart could be involved in degradation of desmin that could be secreted into the blood.…”
Section: Introductionmentioning
confidence: 99%